Malaysian dancescapes - Gonzales, Joseph (Akademi Seni Budaya dan Warisan Kebangsaan (ASWARA), 2013)
With the publication of this book, Joseph Gonzales places himself as one of the leading voices for dance in Malaysia. Writing on topics that span across genres and borders, it reflects his immense experience and shows why he has a global profile. [This book] is essential reading for every dance student, artist, and enthusiast who wishes to discover the multiple layers of artistic experiences that serves to construct the nation of Malaysia.